(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The reign of Elizabeth I is widely recognized in English history as the “Golden Age.” This article analyzes factors of political stability—such as the strong government and relative internal peace ensured by the Elizabethan Religious Settlement—and the unprecedented cultural flourishing that developed on this foundation. The Elizabethan era is distinguished by revolutionary achievements in drama (William Shakespeare and his contemporaries), art, and music, which sharply contrast with the religious conflicts of earlier periods and the crown–parliament tensions of later centuries.